2022
DOI: 10.46235/1028-7221-1183-eoc
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cucurbiturils on cytokine production by peripheral blood mononuclear cells of healthy donors

Abstract: Many drug delivery systems are currently under study, e.g., nanosized cavitands cucurbiturils, which, due to the presence of a cavity, can incorporate drug molecules. Since the immune system is quite sensitive to influence of nanomaterials and other cell-damaging factors, it is necessary to study immunosafety of the new delivery systems, i.e., immunotoxicity and immunomodulatory properties. The aim of this study was to investigate the effect of nanosized cucurbituril cavitands on the cytokine-producing ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…It was demonstrated that different homologues have different effects on the immune system. Based on the obtained data in vitro, CB [8] causes a decrease in the level of IFN-gamma [32], which indicates its possible immunosuppressive effect. Since СB [8] is able to suppress cytokine production, a possible immunosuppressive effect requires further study.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It was demonstrated that different homologues have different effects on the immune system. Based on the obtained data in vitro, CB [8] causes a decrease in the level of IFN-gamma [32], which indicates its possible immunosuppressive effect. Since СB [8] is able to suppress cytokine production, a possible immunosuppressive effect requires further study.…”
Section: Discussionmentioning
confidence: 78%
“…In the case of CB [6], its stimulating effect on the B cells and humoral immune response was demonstrated, since it increased the expression of HLA-DR molecules on B-lymphocytes [21], increased the level of spontaneous production of IL-4 by 1.5 times [32], and also increased in vivo the relative number of B cells in the organs of the immune system. At the same time, the severity of the humoral immune response to a certain antigen after the introduction of CB [6] was reduced, which requires studying the mechanisms of this process.…”
Section: Discussionmentioning
confidence: 98%
“…It was demonstrated that different homologues have different effects on the immune system. Based on the obtained data in vitro, CB[8] causes a decrease in the level of IFN-gamma [ 32 ], which indicates its possible immunosuppressive effect. Since CB[8] is able to suppress cytokine production, a possible immunosuppressive effect requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of CB[6], its stimulating effect on the B cells and humoral immune response was demonstrated, since it increased the expression of HLA-DR molecules on B-lymphocytes [ 21 ], increased the level of spontaneous production of IL-4 by 1.5 times [ 32 ], and also increased in vivo the relative number of B cells in the organs of the immune system. At the same time, the severity of the humoral immune response to a certain antigen after the introduction of CB[6] was reduced, which requires studying the mechanisms of this process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation